Fat and Carbohydrates as Causative Factors of Obesity of Youths at Bulukumba City, South Sulawesi - Muriyati Muriyati; Hamdana Hamdana; Asri Asri; Safruddin Safruddin; Asnidar (Jurnal Penelitian Pendidikan IPA, 2023)
Globally, obesity has entered the epidemic proportion, with at least 2.8 million people dying every year due to obesity, for Indonesia itself the incidence of obesity has also increased significantly in every region with Jakarta's first ranking of 11.4%. The purpose of this study was to determine with certainty that fat and carbohydrates are factors that influence the incidence of obesity in the youth of Bulukumba community. adolescents. Method: Case control study with a total of 155 subjects, cases are people with obesity (IMT/U > +2SD) and controls are people with non-obesity. Independent variables are carbohydrates and fats that they consume. While the dependent variable is the incidence of obesity. Data analysis using Chi-Square test and logistic regression. Results: Factors that are significantly associated (p<0.05) and become causal factors the risk of obesity cases in the community is that fat (OR = 2.34; CI: 1.19-4.57) and carbohydrates (OR = 2.64; CI: 1.34) which were significantly influenced. Conclusion: the youth who have excessive intake of macro foods with high carbohydrate and fat content are more at risk of obesity.